Effectiveness of whitening toothpastes: A review of the literature (Research, Society and Development, 2024)
To carry out tooth whitening, whitening techniques carried out in the office, home whitening and the use of whitening toothpastes stand out. The latter has several agents in its composition that act through chemical, optical and abrasive mechanisms, including: peroxides, blue covarina, abrasives and activated carbon. The study aimed to carry out a bibliographical survey on the effectiveness of whitening toothpastes currently available. This is an integrative review that used the databases Latin American and Caribbean Literature in Health Sciences, Medical Literature Analysis and Retrievel System Online and Scientific Electronic Library Online. The descriptors used were “Toothpastes”, “Tooth Whitening”, “Effectiveness” and “Dental Abrasion” and the Boolean operators associated with the descriptors were AND and OR. A total of 13 articles were selected to prepare this literary review, highlighting that activated charcoal was one of the most abrasive agents, blue covarina was effective in lightening light stains, and silica had a whitening effect due to its abrasive characteristic. From the analysis of the studies found, it was observed that the whitening toothpastes presented were effective in promoting tooth whitening, however, more studies are still needed to discuss the possible repercussions involving the use of these products.